Il paesaggio sociale: essenza e forme degli atti di empatia - De Vecchi, Francesca (Bollettino Filosofico, 2018)
Starting from Stein’s phenomenological account of empathy, I argue for an eidetics of empathy, according to which empathy is one type of acts that, as a whole, is subject to variations of its parts. Eidetics of empathy shows that a variety of acts of empathy, characterised by different degrees of fulfilment, is possible. Moreover, it allows to take into account adequately crucial issues in phenomenology of intersubjectivity and social ontology: in what sense empathy is the «direct perception» of others and their lived experiences? What is «negative empathy»? What are the essential features of sympathy and emotional sharing, as different from empathy?